1986
DOI: 10.1002/art.1780290321
|View full text |Cite
|
Sign up to set email alerts
|

A familial syndrome of pericarditis, arthritis, camptodactyly, and coxa vara

Abstract: CASE REPORTThe parents were descendants of the same great-grandparents (fourth generation). They denied knowledge of individuals in the family, other than their daughters, who had similar problems. Moreover, both parents and 5 of 9 maternal and paternal uncles and aunts were examined by us, and no additional cases were dliscovered. The pedigree and the HLA typing data (A, B, C, and DR) are shown in Figure 1. The HLA typing was performed on heparinized blood Figure 1, number 6), had limitation of movement of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
1

Year Published

1988
1988
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 4 publications
0
31
0
1
Order By: Relevance
“…Laxer et al 7 and Bultlar et al 6 reported three additional patients with this association; although our propositus presented to the local hospital with pericardial rub suggesting pericarditis, follow-up in our institution did not support such findings, raising the possibility that pericarditis may be a reversible phenomenon. Out of 21 patients described in the literature besides our patient, only six had the combination of CAP syndrome.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…Laxer et al 7 and Bultlar et al 6 reported three additional patients with this association; although our propositus presented to the local hospital with pericardial rub suggesting pericarditis, follow-up in our institution did not support such findings, raising the possibility that pericarditis may be a reversible phenomenon. Out of 21 patients described in the literature besides our patient, only six had the combination of CAP syndrome.…”
Section: Discussionmentioning
confidence: 53%
“…This is the first series of this familial arthropathy with a triad of camptodactyly, arthropathy and coxa vara (CAC syndrome) in Saudi Arabia which is to be considered in patients where more than one family member has juvenile arthritis. Ann Saudi Med 1994; 14 (6):479-482. Familial arthropathy associated with congenital camptodactyly has been previously recognized as a definite clinical entity by several authors.…”
Section: Accepted For Publication 19 February 1994mentioning
confidence: 99%
See 2 more Smart Citations
“…Echocardiography showed mild mitral regurge with normal systolic function. This condition was fi rst described in 1986 [4] and is a syndrome of camptodactyly, arthropathy, coxa vara and pericarditis [5]. It may also include congenital cataracts [6].…”
Section: Case Reportmentioning
confidence: 99%